2022
DOI: 10.1021/acs.jafc.2c02824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcumin on Mitochondrial Function, Endoplasmic Reticulum Stress, and Mitochondria-Associated Endoplasmic Reticulum Membranes in the Jejunum of Oxidative Stress Piglets

Abstract: Mitochondria-associated endoplasmic reticulum (ER) membranes (MAMs) are not only critical for the communication between two organelles but also crucial for cellular processes such as energy metabolism, calcium signaling, and mitochondrial dynamics. The effects of curcumin on jejunal mitochondria, ER, and MAMs in piglets under diquat-induced oxidative stress were assessed. Twenty-four piglets (35 days old, weaned at 21 days, 9.54 ± 0.28 kg, six piglets per group) were used in the study: (1) control group; (2) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 48 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…ERMCSs have been proven to play an extremely important role in many diseases such as Alzheimer’s disease and Amyotrophic later sclerosis. , Recently, ERMCSs have drawn increasing interest of researchers in life medicine . According to our previous study, oxidative stress in the intestine may have a close relationship with the mitochondria–ER interaction; however, to our knowledge, data about the role of ERMCSs in intestinal injury induced by DON in piglets have not been found until now …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…ERMCSs have been proven to play an extremely important role in many diseases such as Alzheimer’s disease and Amyotrophic later sclerosis. , Recently, ERMCSs have drawn increasing interest of researchers in life medicine . According to our previous study, oxidative stress in the intestine may have a close relationship with the mitochondria–ER interaction; however, to our knowledge, data about the role of ERMCSs in intestinal injury induced by DON in piglets have not been found until now …”
Section: Introductionmentioning
confidence: 89%
“…20 According to our previous study, oxidative stress in the intestine may have a close relationship with the mitochondria−ER interaction; however, to our knowledge, data about the role of ERMCSs in intestinal injury induced by DON in piglets have not been found until now. 21 Therefore, this experiment was conducted to explore whether ERMCS changes were involved in the mitochondria dysfunction and ERS in the DON-induced intestinal injury in piglets. This approach can provide new insights underlying the mechanisms of DON toxicity in piglets' intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the antioxidative ability of curcumin on livestock animals, curcumin alleviated IUGR jejunum damage in pigs through Nrf2/Keap1 pathway while given as a feed additive in such a way that oxidative stress is reduced along with intestinal development (76,77). Likewise, Li et al reported that curcumin improved oxidative stress conditions in jejunum cell organelles and membranes in piglets (78). A similar study by Zhang et al suggests that curcumin improves meat quality in pigs.…”
Section: Antimicrobial Antioxidant and Anti-inflammatory E Ectsmentioning
confidence: 94%
“…5 DON is assimilated mainly in the jejunum after ingestion of contaminated food. 6 Consequently, the jejunal epithelium is repeatedly exposed to higher DON concentrations than other tissues and becomes the primary DON target. 7 The intestinal epithelial barrier serves as the body's primary barrier against foreign bodies, selectively allowing water, nutrients, and ions to pass through while effectively preventing pathogens from entering the circulation.…”
Section: ■ Introductionmentioning
confidence: 99%